2022
DOI: 10.1093/botlinnean/boac058
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and environmental variability ofDianthus sylvestris(Caryophyllaceae) in the Balkan Peninsula

Abstract: Species with wide ranges often exhibit morphological variability that is mostly shaped by ecological and evolutionary processes, and the resulting diversity is frequently reflected in intraspecific taxonomy. Dianthus sylvestris in the Balkan Peninsula encompasses six subspecies (D. sylvestris subspp. alboroseus, bertisceus, kozjakensis, nodosus, sylvestris and tergestinus), the identification of which is problematic due to a great morphological variability and complex patterns of environmental variation. To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
0
13
2
Order By: Relevance
“…Similarly, while trying to unravel morphological relationships among six Balkan taxa included in the D. virgineus complex, Terlević & al. (2023) found two main morphological units, incongruent with traditional taxonomy, that were mainly differentiated by the shape of their epicalyx scales and their calyx length (along with some petal features that are not considered in the present work). Furthermore, the combination of different shape and length of calyx teeth has been strictly linked to the diverse shape of floral buds found between D. virgineus and D. inodorus from type localities (Domina & al., 2021b).…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…Similarly, while trying to unravel morphological relationships among six Balkan taxa included in the D. virgineus complex, Terlević & al. (2023) found two main morphological units, incongruent with traditional taxonomy, that were mainly differentiated by the shape of their epicalyx scales and their calyx length (along with some petal features that are not considered in the present work). Furthermore, the combination of different shape and length of calyx teeth has been strictly linked to the diverse shape of floral buds found between D. virgineus and D. inodorus from type localities (Domina & al., 2021b).…”
Section: Discussioncontrasting
confidence: 48%
“…Terlević & al. (2023) showed that petals size and shape varied significantly along the Balkan Peninsula, but without fully mirroring current taxonomy. However, difference in petal denticulation allowed a discrimination between D. sylvestris subsp.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Detailed agro-morphological characterization and assessment of patterns of genetic variability based on quantitative and qualitative traits is the rst and crucial step in describing available genetic resources and their e cient use in breeding programs (Balkaya and Yanmaz 2005;Oumata et al 2023). However, although agro-morphological traits can be controlled at the genetic level, they may be nonspeci c and non-polymorphic, and their variation could be strongly in uenced by environmental factors (Choudhury et al 2022;Petit et al 2020;Terlević et al 2023). In contrast, DNA-based molecular markers are stable, intact, abundant in the genome, and free from environmental in uences.…”
Section: Introductionmentioning
confidence: 99%